Antimicrobial Evaluation And Phytochemical Analysis Of A Known Medicinal Plant Samanea Saman (Jacq.) Merr. Against Some Human And Plant Pathogenic Bacteria And Fungi - THIPPESWAMY, S.,; PRAVEEN, P.,; MOHANA, D.C.,; MANJUNATH, K., (International Journal of Pharma and Bio Sciences, 2011)
The present investigations evaluate the antimicrobial efficacy of six different solvent extracts and isolated constituents of Samanea saman (Jacq.) Merr. against 21 microorganisms. Our result revealed that, the methanol extract showed a highest antibacterial activity with zone of inhibition ranging from 11.0mm to 30.5mm at 1mg/ml concentration. The MIC value of the methanol extract for the tested bacteria ranged between 15µg/ml to 500µg/ml. The most susceptible organism in the present investigation was Streptococcus faecalis (MIC 15µg/ml) followed by Staphylococcus aureus (MIC 62µg/ml), while the most resistant was Proteus vulgaris (MIC 500µg/ml). The highly significant antifungal activity against all the fungi was observed in methanol extract with percentage of inhibition ranging from 20.4% to 81.6% depending upon fungal species at 1mg/ml concentration. The IC50 value of the methanol extract ranged from 0.3mg/ml to 5mg/ml. Among the tested fungi, Fusarium moniliforme (IC50 0.3mg/ml) was highly sensitive and Aspergillus tamari (IC50 5mg/ml) was least sensitive.